Utilization of Anthocyanin Extracted from Pletekan (Ruellia tuberosa L.) in Determination Soil pH - Putri, Olivia Damayanti; Pertiwi, Dharmi Wimi; Widjajani, Bakti Wisnu (Journal of Tropical Horticulture, 2019)
Pletekan (Ruelliatuberosa L.) is a flowering plant that grows wild. Pletekan has blue-purple flowers, containing the anthocyanin as its specific color. Anthocyanin is an organic material that can be used as an indicator of natural acid alkali, because the color of anthocyanin can ensure specific color changes when it reacts with materials at a certain pH as well. This research aimed to utilize anthocyanin extracted from pletekan as a determinant of soil pH. The used method was maceration extraction by soaking fresh pletekan flowers using maceration solvent (methanol acidified by HCl 1%) for 2-3 days. Concentrated anthocyanin extracts needed to be diluted with extracts that had not been concentrated so that the resulted color changes were more specific. The anthocyanin mixture was applied to pH 1-12 buffer solution and in acid and alkaline soil samples. The soil was dissolved using aquadest at a ratio of 1: 2, the soil was left to settle to get water. The color change in the tested water of soil sample was adjusted to the color of the buffer solution and pH meter. Results showed that color change of soil sediment-water which was dropped by natural pH indicators needed more indicator drops such as 2-3 levels than was color changes caused by the buffer solution.